Clinical and Microbiological Characteristics of Visceral Leishmaniasis Outbreak in a Northern Italian Nonendemic Area: A Retrospective Observational Study. (23rd November 2016) - Franceschini, E.; Puzzolante, C.; Menozzi, M.; Rossi, L.; Bedini, A.; Orlando, G.; Gennari, W.; Meacci, M.; Rugna, G.; Carra, E.; Codeluppi, M.; Mussini, C.
Abstract : Background . Visceral leishmaniasis (VL) caused by Leishmania infantum is endemic in the Mediterranean area. In the last decades a northward spread of the parasite has been observed in Italy. This paper describes a VL outbreak in Modena province (Emilia-Romagna, Northern Italy) between 2012 and 2015. Methods . Retrospective, observational study to evaluate epidemiological, microbiological characteristics, and clinical management of VL in patients referring to Policlinico Modena Hospital. Results . Sixteen cases of VL occurred in the study period. An immunosuppressive condition was present in 81.3%. Clinical presentation included anemia, fever, leukopenia, thrombocytopenia, and hepatosplenomegaly. Serology was positive in 73.3% of cases, peripheral blood PCR in 92.3%, and bone marrow blood PCR in 100%. Culture was positive in 3/6 cases (50%) and all the isolates were identified as L. infantum by ITS1/ITS2 sequencing. The median time between symptom onset and diagnosis was 22 days (range 6–131 days). All patients were treated with liposomal amphotericin b. 18.8% had a VL recurrence and were treated with miltefosine. Attributable mortality was 6.3%. Conclusions . VL due to L. infantum could determine periodical outbreaks, as the one described; thus it is important to include VL in the differential diagnosis of fever of unknown origin, even in low-endemic areas.